Natural Sciences in Elementary Classes _ Technology for Improving Aesthetic Education of Students in Teaching (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This in the article initial in classes natural sciences in teaching of young people aesthetic education formation of the problem to be studied and students for methodical of the rules main scope identify students _ environment to love in teaching natural of sciences place of students aesthetic views, behavior, natural science classes to the students aesthetic education to give through them worldview formation possibilities sure.